Rapid methodology to screen flame retardants in upholstered furniture for compliance with new California labeling law (SB 1019). (June 2016) - Petreas, Myrto; Gill, Ranjit; Takaku-Pugh, Sayaka; Lytle, Eric; Parry, Emily; Wang, Miaomiao; Quinn, John; Park, June-Soo
Abstract: In response to concerns regarding the widespread use of flame retardants, the California Legislature passed a law (SB1019) requiring labels on furniture products to indicate whether they do or do not contain flame retardants. To support the enforcement of the new law, our laboratory developed a step-wise, screening approach to test for brominated (BFR) and phosphorus-based flame retardants (OPFRs) in several types of furniture components (foam, fabric, batting, plumage, etc.). We used X-Ray Fluorescence (XRF) to screen for the presence of Br (and other elements) and Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES) to identify and measure the concentration of P (and other elements). The same samples were also extracted by dichloromethane using sonication and analyzed by a single injection into a Gas Chromatograph – Tandem Mass Spectrometer to obtain concentrations of specific BFRs and OPFRs. Our approach showed excellent screening potential for Br and Sb by XRF and for P by ICP-OES, with both tests having predictive values of a negative equal to 1. To explore and screen for flame retardants in products not included in our current list of target chemicals, we used Liquid Chromatography/Time-of-Flight Mass Spectrometry operated with electrospray ionization, to identify additional flame retardants to be incorporated in quantitative methods. We are making all our methodologies public to facilitate simple and low cost methods that can help manufacturers and suppliers have their products tested and correctly labeled, ultimately benefitting the consumer. Graphical abstract: Highlights: California law (SB1019) requires disclosing the presence of flame retardants in furniture. We compared low cost screening and advanced techniques to identify flame retardants. XRF can be reliably used to screen Br and Sb. ICP-OES can be reliably used to screen and quantitate P. We use GC–MS/MS to report BFRs, OPFRs and LC-TOF to explore additional flame retardants.